ANALISIS KEMAMPUAN PEMENGGALAN KATA SISWA KELAS III SD NEGERI 37 PEKANBARU - Yuyun Pertiwi Yuyun Pertiwi; otang kurniaman otang kurniaman; gustimal witri gustimal witri (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The background of this study is that students do not yet know how to write the decapitation correctly. This study aims to describe the ability to decapitate the third grade students of SD Negeri 37 Pekanbaru. The type of research used is quantitative descriptive. The population in this study were third grade students of SD Negeri 37 Pekanbaru. The sample used in this study was 155 students. The data collection technique used by this researcher is a written test technique. The written test used in this study is in the form of a short essay with a number of 30 questions. Analysis of the data used in this study is quantitative or statistical. The results showed that the ability to decapitate the third grade students of Pekanbaru Elementary School 37 in the category of Less or equal to 49.70. This is evidenced by the acquisition of data, namely: Obtaining an average score of the ability to decapitate the first indicator of 60.96 with the category "Enough", the average score of the ability to decapitate the ability of the second indicator is 34.14 with the category "Less", while the average score of the decapitation ability on the third indicator is 54.68 with the category "Enough".